Modelo de negocio para la producción y comercialización de jeans de la empresa Camila Jeans en Ambato, 2024 - Limache Agualongo, Ángel Vinicio (2024)
The objective of the research was to develop a Canvas business model for the jeans company Camila Jeans, located in the city of Ambato. For this, a mixed paradigmatic modality was used with an emphasis on the quantitative approach. The type of research was nonexperimental with a cross-sectional design and a descriptive scope. Techniques such as surveys and interviews were used, and the analytical-synthetic method was applied to break down the project into different studies and process the information obtained. In addition, bibliographical research was carried out to provide a theoretical basis for the project, analysing scientific articles, books and indexed journals that contributed to the development of the project. Similarly, the historical-logical method was used to obtain historical data on the company. At the empirical level of knowledge, the documentary analysis method was applied to review information related to Canvas-type business models. This model is characterised by the schematization of the company on a canvas, capturing ideas, hierarchical structure and innovation processes. The main achievements were: the theoretical systematisation of the projects, the analysis of the level of acceptance of potential customers for the jeans and the determination of the effective demand in the market study. In addition, the production process and production costs were established through the technical study, the organic-functional structure of the company was defined, and the economic-financial data, such as the total investment, were compiled. Finally, the feasibility of the project was evaluated through feasibility indicators.